« Coume li chivalié d’antan avèn voua nosto vido au triounfle d’uno Idèio. » Folco de Baroncelli, du Félibrige à la Nacioun Gardiano, d’après les archives d’auteur du Palais du Roure (Avignon) - Marjolaine Raguin (Revue des Langues Romanes)
Folco de Baroncelli, considered to be the inventor of a certain idea of the Camargue, was an indefatigable defender of a territory, its language and its customs, a young félibre coming from a noble family, the baile of L'Aiòli of Frédéric Mistral, the founder of the Nacioun gardiano, and also an unknown prose writer and poet. His literary and documentary archives kept at the Palais du Roure (Avignon), after having been placed under the good care of Jeanne de Flandreysy, inform the critic about the author at his table and his thought, developed over time. The presence in these collections of drafts, edited versions, translations from Provençal into French, first editions of some of his literary works, militant texts, and speeches, as well as unpublished works, allows for a necessary clarification and, based on a few examples of genetic criticism, a plea for an in-depth study of the content and critical editions that will give pride of place to the process of genesis of his texts.